1972
DOI: 10.1021/jo00985a002
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective syntheses. VIII. Retentive nucleophilic displacements of .alpha.-substituted alkylferrocenes

Abstract: Ferrocenylethane derivatives with suitable leaving groups [chloro, acetate (9), trimethylammonium (2)] in the a position generally undergo nucleophilic substitutions with complete retention of configuration and are useful for the preparation of a variety of chiral ferrocene derivatives. Stereochemical and kinetic evidence indicates an SnI mechanism via a configurationally stable -ferrocenylethyl carbonium ion intermediate. Departure of the leaving group and entry of the substituting nucleophile involve analogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 280 publications
(89 citation statements)
references
References 14 publications
6
82
1
Order By: Relevance
“…Another remarkable feature is that nucleophilic displacement reactions at the α-position proceed with complete retention of configuration [30]. This is due to the stabilization of the carbenium ion via an overlap with an iron lone pair (13A).…”
Section: Synthetic Routes Towards Chiral 12-disubstituted Pn-ferrocmentioning
confidence: 99%
“…Another remarkable feature is that nucleophilic displacement reactions at the α-position proceed with complete retention of configuration [30]. This is due to the stabilization of the carbenium ion via an overlap with an iron lone pair (13A).…”
Section: Synthetic Routes Towards Chiral 12-disubstituted Pn-ferrocmentioning
confidence: 99%
“…A crown ether containing a ferrocene unit, pentaoxa [13]ferrocenophane, 8, was reported by Saji and Kinoshita. 6 Electrochemical studies showed an abrupt decrease in its cation binding constants by electrochemical oxidation of ferrocene.…”
Section: Choice Of Ferrocene As the Redox Switchmentioning
confidence: 89%
“…Compounds 13-18 were prepared by a Williamson reaction 13 that takes advantage of the extraordinary stability of the ␣-ferrocenylmethyl carbocation.…”
Section: Compound Synthesesmentioning
confidence: 99%
“…In addition, there is a steadily increasing interest in these compounds because of their important role as chiral ligands in homogeneous asymmetric catalysis [3] . Due to nucleophilic substitution reactions, which take place under complete retention of the configuration, a broad variety of ligands can be synthesized based on (1-ferrocenylalkyl)amines [4] . These ferrocenylamines have been conveniently prepared through the diastereoselective ortholithiation of optically active N,N-dimethyl- (1-ferrocenylethyl)amine (e.g.…”
Section: Introductionmentioning
confidence: 99%